Performance evaluation of IEEE 802.15.4 sensor networks in industrial applications. (19th February 2014) - Du, Wan; Navarro, David; Mieyeville, Fabien
Summary Wireless sensor networks have been widely applied in industrial applications especially since the release of IEEE 802.15.4 standard. By participating in an automobile project in which an IEEE 802.15.4 based sensor and actuator network is deployed to measure and control the vibrations of an automotive system, we need to study many metrics of IEEE 802.15.4 sensor networks (e.g., packet delivery rate, latency, and energy consumption) under various sampling rates. In order to provide detailed modeling of hardware and software as well as network behaviors on each sensor node, we conduct plenty of experiments on a SystemC‐based wireless sensor networks simulator IDEA1, which supports the hardware and software co‐simulation of sensor nodes with certain flexibility of abstraction level. Compared with the existing works on performance evaluation of IEEE 802.15.4 protocols, the main contributions of this paper are the comprehensive studies of both beacon‐enabled and nonbeacon‐enabled modes under various parameter settings and the beacon tracking synchronization mechanism in the IEEE 802.15.4 standard, which is ignored in most previous works. Additionally, the in‐depth analysis of simulation results enables us to find the best parameter configurations to different traffic loads and application requirements, which can be used as general experiences for other applications.Copyright © 2014 John Wiley & Sons, Ltd.